(untitled) (Journal of Hama University, 2024)
Synovial plicae are synovial folds or a shelf of tissue that may be found as intra articular structures within the knee joint. They are remnants of incomplete resorption of mesenchymal tissue during fetal development. Synovial plicae, if present, are supposed to be non-pathological and asymptomatic, however if they are exposed to special events like direct trauma or repeated activities, they may be inflamed and become fibrosed and rigid and irritates the synovium of the underlying femoral condyle resulting in secondary mechanical synovitis and chondromalacia leading to what is known as plicae syndrome of the knee. Inspite plicae syndrome is always suspected on clinical bases and can be clearly visualized by arthroscopic application, still diagnostic imaging by MRI play important role in the evaluation and diagnosis of this pathological condition. The aim of this article: is to provide an overview of the imaging appearances of synovial plicae of the knee on magnetic resonance imaging (MRI) and arthroscopy, to report the radiologic, arthroscopic, and clinical appearance of a rare case of lateral synovial plicae along with its response to conservative and surgical treatment, and review previous articles.